East Asia Summit, Phase II: Back to Confidence Building? - Pang, John (2016)
The EAS started with a community building vision. With US participation and rising strategic tensions, it has become a regional confidence building and conflict-prevention mechanism. This is a realistic role for the EAS that ASEAN should embrace and sharpen.